2013
DOI: 10.1088/1758-5082/5/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red laser ablative micromachining of parylene-C on SiO 2 substrates for rapid prototyping, high yield, human neuronal cell patterning

Abstract: Cell patterning commonly employs photolithographic methods for the micro fabrication of structures on silicon chips. These require expensive photo-mask development and complex photolithographic processing. Laser based patterning of cells has been studied in vitro and laser ablation of polymers is an active area of research promising high aspect ratios. This paper disseminates how 800 nm femtosecond infrared (IR) laser radiation can be successfully used to perform laser ablative micromachining of parylene-C on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…This was extended by Unsworth who patterned rat primaries to the single cell level on ultra-thin parylene-C [37]. Unsworth also demonstrated how parylene-C could be used to pattern the hNT neuron [38] and hNT astrocyte [39] derived from the human teratocarcinoma cell line to the single cell level and Raos demonstrated how infra-red, laser ablated parylene-C [40] could be used for rapid pattern prototyping using hNT astrocytes. This work has been further extended by Hughes [41] who demonstrated how to modulate the pattern adhesion properties for HEK293 cells on parylene-C.…”
Section: Cell Patterning and Biomaterials Parylene-cmentioning
confidence: 95%
“…This was extended by Unsworth who patterned rat primaries to the single cell level on ultra-thin parylene-C [37]. Unsworth also demonstrated how parylene-C could be used to pattern the hNT neuron [38] and hNT astrocyte [39] derived from the human teratocarcinoma cell line to the single cell level and Raos demonstrated how infra-red, laser ablated parylene-C [40] could be used for rapid pattern prototyping using hNT astrocytes. This work has been further extended by Hughes [41] who demonstrated how to modulate the pattern adhesion properties for HEK293 cells on parylene-C.…”
Section: Cell Patterning and Biomaterials Parylene-cmentioning
confidence: 95%
“…Another method for Parylene removal includes laser ablation (266 nm), one of the first techniques employed for Parylene etching to expose electrode sites. Infrared (800 nm) and UV (248 nm) laser ablation of Parylene films (100 nm thickness) on wafer for direct writing were investigated for precise cell patterning . However, UV laser ablation was found to induce UV‐based photooxidation of the Parylene substrate and render the surface unideal for cell patterning applications .…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Infrared (800 nm) and UV (248 nm) laser ablation of Parylene films (100 nm thickness) on wafer for direct writing were investigated for precise cell patterning . However, UV laser ablation was found to induce UV‐based photooxidation of the Parylene substrate and render the surface unideal for cell patterning applications . Manual removal of Parylene films has also been demonstrated, where a pre‐coating of release agents, such as 2% Micro‐90 lab cleaning solution (International Products Corporation, Burlington, NJ) on the substrate as well as immersion in water aided in the removal of the film without damage.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…However, for the multiple pulse low power IR ablation, our recent study in [19] revealed that ragged veneers where also present around the edges of the parylene-C strips as opposed to the straight edges that occurred with the single pulse high power ablation. Hence, we elected to use the single pulse high power due to optimize the high resolution of the edges of the parylene-C strips.…”
Section: B Ir Laser Ablative Patterningmentioning
confidence: 96%